Effect of agility ladder training with a cognitive task (dual task) on physical and cognitive functions: a randomized study - Castillo de Lima, Vivian; Castaño, Luz Albany Arcila; Sampaio, Ricardo Aurélio Carvalho; Sampaio, Priscila Yukari Sewo; Teixeira, Camila Vieira Ligo; Uchida, Marco Carlos (Frontiers in Public Health, 2023)
Introduction Agility training (AT) is used to improve neuromuscular performance and dynamic balance, which are crucial for the physical function of older adults. Activities of daily living, which decrease with age, involve tasks that simultaneously require motor, and cognitive abilities and can be considered dual tasks. Methods This study investigates a training program's physical and cognitive effects using an agility ladder on healthy older adults. This program consisted of 30-min sessions twice per week and lasted for 14 weeks. The physical training included four different sequences with progressive difficulty levels, while the cognitive training (CT) included different verbal fluency (VF) tasks for each physical task. Sixteen participants (mean age of 66.9 ± 5.0 years) were allocated to two groups: AT alone (AT) and dual-task training (AT combined with CT [AT + CT]). Assessments were performed before and after 14 weeks of interventions using physical functional tests (e.g., Illinois agility test, five times sit-to-stand test, timed up and go [TUG], and one-leg stand) and cognitive tests (cognitive TUG, verbal fluency, attention, and scenery picture memory test). Results After this period, both groups had significant differences in physical performance, muscle power, agility, static and dynamic balance, and short-term memory, whereas only the AT + CT group improved phonological verbal fluency, executive function (TUG combined with a cognitive task), attention (trail-making test-B), and short-term memory (scenery picture memory test). Conclusion Indicating that only the group that received direct cognitive training had better enhanced cognitive function. Clinical trial registration www.ClinicalTrials.gov, identifier: RBR-7t7gnjk.